Software Process Assessment and Certification: The Reference Standard and Weight Determination using QFD-AHP - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz; Ahmad, Mazida (2018)
Software process certification has become as one of the mechanisms for ensuring the quality of software. To certify that the software process implemented by an organization is good, assessors need to make decision based on various evaluation criteria that need to be weighted, besides numerous software process practices. Thus, it is a complex procedure to be performed. Hence, in this study, Quality Function Deployment (QFD) and Analytic Hierarchy Process (AHP) has been integrated to articulate the reference standard for the software process assessment and certification. QFD is adapted to organize “what” and “how” to assess software process while AHP is utilized to formulate method in determining “weight value” for each evaluation criteria. Combination of both approaches ensure that the assessment criteria are systematically organized and the decision is not made arbitrarily. This paper discusses about the reference standard used for software process assessment and certification. It contributes to the body of knowedge in the Software Certification area, since both QFD and AHP are newly introduced in the area.